HUBUNGAN PENERIMAAN DIRI DAN DUKUNGAN SOSIAL SUAMI TERHADAP KECEMASAN IBU PRIMIGRAVIDA MENGHADAPI PERSALINAN - Salakory, Jacomina Anthonete (Jurnal Kebidanan, 2024)
Anxiety before childbirth is a common psychological response experienced by primigravida pregnant women. Factors such as self-acceptance and social support, particularly from the husband, play an important role in reducing this anxiety. This study aims to analyze the relationship between self-acceptance, husband’s support, and anxiety in primigravida pregnant women in the working area of Puskesmas Amahusu. The research design used is descriptive analytic with a cross-sectional approach. The results indicate that good self-acceptance and good husband support are significantly related to lower levels of anxiety. The P-value for self-acceptance (P = 0.002) and husband support (P = 0.002) suggest that these two factors have a significant influence on the anxiety levels of primigravida pregnant women. This study recommends the importance of enhancing emotional support from partners and strategies to improve self-acceptance in pregnant women in order to reduce anxiety before childbirth.